CASE REPORT –A RARE CASE OF EARLY PREGNANCY COMPLICATED BY BILATERAL PSOAS ABSCESS - SHASHIKALA .G.,; SUMATHI.K.,; SARASWATHI.K., (International Journal of Pharma and Bio Sciences, 2013)
Psoas abscess, especially bilateral, is a rare clinical condition, which may be missed in day to-day clinical practice by general practitioners, unless there is a high clinical suspicion. And since occurrence in pregnancy is even rarer, its prompt diagnosis and effective management can result in good outcome. The following case report is a rare case of bilateral Psoas Abscess during early pregnancy and its management.